UPAYA MENINGKATKAN HASIL BELAJAR SISWA TENTANG PENJUMLAHAN BILANGAN PECAHAN DENGAN MENGGUNAKAN MEDIA GAMBAR LUAS DAERAH DI KELAS IV SD NEGERI 23 SUNGAISELAN - Rohmi Hidayah; Asyraf Suryadin; Dodi Pranata (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to improve the ability to add fractions among fourth-grade students at SD Negeri 23 Sungaiselan through the use of area model image media. The research was motivated by the low mathematics learning outcomes, particularly in fraction material, due to the continued use of conventional teaching methods and minimal use of concrete learning media. The study employed a Classroom Action Research (CAR) method using the Kemmis and McTaggart model, conducted in two cycles, each consisting of the planning, action, observation, and reflection stages. The research subjects were 20 students, with success indicators set at a minimum score of 70 per student and a classical mastery level of 85%. The results showed a significant improvement in learning outcomes: in the pre-cycle, only 15% of students achieved mastery with an average score of 43.5, in cycle I, mastery increased to 65% with an average score of 63.5, and in cycle II, mastery reached 90% with an average score of 83.5. In addition to improved scores, students demonstrated higher active participation, increased learning motivation, and better understanding of fraction concepts. The study concludes that the use of area model image media is effective in helping students understand fraction addition concepts, while also creating an interactive, contextual, and engaging learning environment.